THE BASIC DESIGN OF OPTIMAL TECHNOLOGICAL PROCESSES OF RAILWAY CARS REPAIR - Kulichenko, A. Ya. (Science and Transport Progress, 2009)
For simplification, speedup and cost reduction of preparation of repair-reconstruction work the author offers to introduce the typology of technological processes on the basis of developed by him classification of wagon parts, putting into a basis of development of the technological processes the techno processes for standard details, which inherent only to the railway rolling stock.